THE RELATIONSHIP AMONG THE LEARNING PREPARATION AND ATTENTION OF PARENTS WITH LEARNING MATHEMATICS OUTCOMES OF STUDENTS CLASS VII - Hidayat Nursyawaludin; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This study is based on students' mathematics and low readiness study's poor learning outcome, and parents' lack of attention. Inadequate learning readiness involving students still depends on the teacher's instruction. Students feel embarrassed and afraid to ask when the learning and the parents still assume that education and attention to the child are the school's responsibility. This study aims to determine whether or not a positive and significant relationship between the readiness of learning and parents' attention with the results of learning mathematics students VII State Junior High School (SMP Negeri) 3 Wates Kulon Progo District Year 2017/2018. This study's population is the students of grade VII of SMP Negeri 3 Wates Kulon Progo Regency for the academic year 2017/2018, which consists of VIIA, VIIB, VIIC, and VIID grades totaling 138 students. Obtained class VIIB as a class of research samples with random sampling technique. Data collection techniques used questionnaire method to obtain data readiness study and parents' attention and test methods to obtain data learning mathematics. Test of research instrument done is a test of validity, a test of different power, and reliability test. The prerequisite analysis test includes the normality test, linearity test, and independence test. Data analysis using product moment analysis and multiple linear regression analysis. The results showed a positive and significant relationship between the readiness of learning and parents' attention with learning mathematics students VII SMP 3 Wates Kulon Progo District Year 2017/2018. It is shown by >  that is 4,139> 3,310 with R = 0,459 and R2 = 0,211 with Y = 24,865 + 0,357  + 0,252 , with RC  = 64,023% and RC = 35,977%, EC = 13,492% and EC  = 7,582%.